Validity of the Comprehensive Learning Test for Diagnosis of Specific Reading or Mathematical Disorders - Kim, Sujin; Kim, Woo Young; Lee, Hyunju; Lee, Eun Kyung; Huh, Hannah; Youn, JungHae; Jung, Jaesuk; Suh, Cheon Seok; Kim, Bongseog; Yoo, Hanik (Journal of the Korean Academy of Child and Adolescent Psychiatry, 2025)
This study aimed to verify the diagnostic validity of the Comprehensive Learning Test (CLT) for children and adolescents with reading (RD) or mathematical disorders (MD). To evaluate the diagnostic validity of the CLT-Reading (CLT-R) and CLT-Math (CLT-M), a total of 284 participants (142 in RD and 142 in the control group) and 184 participants (92 in MD and 92 in the control group) were recruited, respectively. The control groups were selected through one-to-one matching based on sex and grade. For the CLT-R, three criteria were established using accuracy and fluency measures (one impairment, one impairment or one borderline, and one impairment or two borderline scores). Two criteria were established for the CLT-M (one impairment, one impairment or one borderline score). The sensitivity, specificity, positive predictive value, and negative predictive value (NPV) were calculated for each criterion. In the CLT-R, when no impairment or borderline score presented in accuracy, applying the fluency criterion of "one impairment or one borderline score" yielded the highest diagnostic validity for RD, with a sensitivity of 0.963 and an NPV of 0.991. In the CLT-M, when no impairment or borderline score in accuracy, was present applying the fluency criterion of "impairment or borderline" resulted in the highest diagnostic validity for MD, with a sensitivity of 0.814 and specificity of 0.966. These findings support that the CLT-R and CLT-M are highly valid tools for diagnosing RD and MD.